Anaesthetists’ practice of awake fibreoptic intubation in adult patients - Van Rooy, Elizabeth (My University, 2018)
Background Awake fibreoptic intubation (FOI) remains the gold standard management of the anticipated difficult airway. An organised approach will ensure success and patient comfort. Training has to be rigorous to instil confidence. Exposure, practice and level of confidence of awake FOI in the Department of Anaesthesiology at the University of the Witwatersrand (Wits), is not known. Methods Anaesthetists were surveyed with an anonymous self-administered questionnaire. A total of 130 questionnaires were distributed at departmental academic meetings over five months and 126 (96.9%) questionnaires were returned. Results The majority (41.2%) had only performed one to five awake FOIs, 12.7% had performed 21 to 50, but 13.5% had never performed any. The majority were trained on asleep (39.8%) and awake (31.9%) patients. Only 20.4% had manikin, and 4.2% simulator training. While 58.7% had reasonable levels of confidence, 41.3% had low confidence. Midazolam (35.0%) and fentanyl (26.7%) were the most commonly used drugs for sedation followed by remifentanil (16.1%) and dexmedetomidine (12.2%). All topicalised the airway prior to awake FOI. Lignocaine 2% was the drug of choice (72.2%). Techniques included application of soaked swabs (23.4%), spray (22.8%), spray-as-you-go (18.7%), nebulisation (16.4%), gel or ointment (8.8%), transtracheal block (6.4%) and gargle (2.9%). Conclusion Anaesthetists in the Wits Department may not be adequately exposed to awake FOI and demonstrated a marked variability in sedation and topicalisation practices.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Anaesthesiology. Johannesburg, 2016.
Keywords: Fibreoptic Intubation; Anesthetists